Пристапот до финансирање на малите и средните претпријатија: улогата и интервенциите на државата - Димовска, Ефимија (Економски факултет, УКИМ, Скопје, 2013)
The aim of this research is to provide a deep analysis of how to enhance access to finance of SME’s in the Republic of Macedonia. The starting point of the research is the wide accepted evidence that the SME sector is one of the most important drivers of the economy in each country. SME’s participate with a high percentage in the GDP generation, new jobs creation, increase of export, innovation of products and services. In addition, many studies and research have concluded that access to finance remains to be a major concern and main obstacle for SMEs growth and development in the SEE countries. The lack of external financing limits the capacity of firm to expand their operation, to improve technology and productivity and even question its continued existence. Bank loans are the main source of external financing of SMEs in the region. However, there are many factors as higher administrative costs and risks involved in lending to SMEs that reduce banks’ willingness to lend to them. Also, lack of collateral and borrower information is frequently reason for credit rejection. Therefore, many governments have acknowledged the importance of implementing various policies and programs aimed to support SMEs and their development, particularly in the time of global financial crises. Several empirical examples have shown that successful realization of carefully designed government instruments would contribute to the enhanced access to finance of SMEs, thereby leading to new investments, job creation and economic growth. However, the Governemnt policies regarding this issue should be based on detail analysis of both, supply and demand side. Therefore, the research, based on empirical analysis of secondary data and conducted survey, focuses on four main areas: (i) why access to finance of SME is severely constrained; (ii) what is the actual situation on the supply – side, with concentration on the banking sector; (iii) how policy makers deal with the problem; and (iv) what are the effects of implemented measures.
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Михаил Петковски.
Keywords: SMEs, access to finance, bank loans, Government programs